Big Nate Lives It Up: Big Nate #7 #7 Big Nate - Peirce, Lincoln (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2015)
"As his school's centennial is coming up, Big Nate is stuck showing the dorky new kid around"--.
Keywords: Behavior -- Fiction; Schools -- Fiction; Friendship -- Fiction; Middle schools -- Fiction; Humorous fiction